FRANCOISM AND IBERO-AMERICA THROUGH SOCIAL SECURITY AGREEMENTS. AN APPROACH FROM SPAIN - Revuelta Sierra, Guillermo (Revista de Historia Social y de las Mentalidades, 2020)
From the sixties to the first half of the seventies of the 20th century, Spanish emigration shot up to European countries, while it decreased in Latin American countries. At that time, however, social security agreements were signed between the Franco regime and the Ibero-American states, establishing new forms of relations between the two parties. Our purpose is to explain the reasons why they were signed and to analyse their benefits. As a more noteworthy novelty, this paper studies the documentation of the Official Bulletin of the Spanish Parliament (BOCE), practically ignored by historiography.